2011
DOI: 10.1007/s00484-011-0481-y
|View full text |Cite
|
Sign up to set email alerts
|

Heat-related mortality in the Florentine area (Italy) before and after the exceptional 2003 heat wave in Europe: an improved public health response?

Abstract: High ambient temperatures have been associated with increased mortality across the world. Several studies suggest that timely preventive measures may reduce heat-related excess mortality. The main aim of this study was to detect the temporal modification of heat-related mortality, in older adults (aged 65-74) and in elderly ≥75 years old, in the Florentine area by comparing previous (1999-2002) and subsequent (2004-2007) periods to the summer of 2003, when a regional Heat-Health Warning System (HHWS) was set u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 26 publications
5
51
0
1
Order By: Relevance
“…81 The implementation of a regional heat-health warning system was associated with a decrease of the excessive heat effect on mortality also in Tuscany, Italy. 82 However, an important residual risk remains that needs to be more vigorously addressed by public health authorities in light of the expected increase in the frequency and severity of heat waves and the aging of the population. Because a warmer climate is predicted in the future, the incidence of heat waves should increase, and more comprehensive measures, both medical and social, should be adopted to prevent the effects of extreme heat on the population, particularly the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…81 The implementation of a regional heat-health warning system was associated with a decrease of the excessive heat effect on mortality also in Tuscany, Italy. 82 However, an important residual risk remains that needs to be more vigorously addressed by public health authorities in light of the expected increase in the frequency and severity of heat waves and the aging of the population. Because a warmer climate is predicted in the future, the incidence of heat waves should increase, and more comprehensive measures, both medical and social, should be adopted to prevent the effects of extreme heat on the population, particularly the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…From the physiological point of view, the organism in old age can not fully compensate meteorological effects in a natural way due to a multitude of factors (Morabito et al, 2012). Indeed, increases in mortality of the elderly tend to be among the largest in heat episodes (e.g.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Many authors have investigated the relationship between extreme weather events (heat waves) and health, underlining the benefits of heat-warning systems [22,25]: this study shows the relationship between weather and health during ordinary weather conditions, and the benefits of supporting health structures with biometeorological forecasts.…”
Section: Introductionmentioning
confidence: 97%
“…Bassil and collaborators [4,5] suggested that 911 calls could capture a greater proportion of the burden of illness than ED admissions. Emergency call data were only analysed in very few studies, and there the main purpose was to investigate the circadian variation of emergency calls [8] or the relationship between weather and extreme health events [4,6,7,21,22]. Other studies investigated the relationship between weather and phone calls, especially to understand the relationship between weather and emotional states [23,24].…”
Section: Introductionmentioning
confidence: 99%